Inspection and Improvement of Lightning Protection System for the Guyed-Mast Tower a Case Study of PHRAO Hospital in Chiang Mai - พิทักษ์วงศ์ บัณฑูร; วิไลลักษณ์ ภีมภิวัฒน์; ปันตา สุทธิพงศ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Hospitals are among the places that are affected by lightning phenomena. Lightning bolts tend to reach the top of buildings and find their way to the ground in an uncontrolled manner through guyed-mast towers, creating electromagnetic impulses that immediately cut off communication systems. Therefore, lightning protection system for guyed-mast towers has been inspected and improved to comply with TISI standards 022001-22, 022014-22 and ITU-T K.56, ITU-T K.112. After improving the lightning protection system, it can be concluded that the resistance value of the radio tower is not an important issue, but reducing the impact of lightning and the increased ground potential rise that goes outside the communication station is a more important issue. It is necessary to design the grounding rods taking into account the effective length of the grounding rods, improving the specific resistance of the soil to be low enough for all seasons, increasing the number of grounding rods to improve the impulse coefficient ratio, and have the resistance of grounding rods 5 ohms, using a Faraday cage lightning protection system by rolling sphere model.